2021
DOI: 10.1038/s41419-021-03655-2
|View full text |Cite
|
Sign up to set email alerts
|

AMPK activation by ASP4132 inhibits non-small cell lung cancer cell growth

Abstract: Activation of adenosine monophosphate-activated protein kinase (AMPK) is able to produce significant anti-non-small cell lung cancer (NSCLC) cell activity. ASP4132 is an orally active and highly effective AMPK activator. The current study tested its activity against NSCLC cells. In primary NSCLC cells and established cell lines (A549 and NCI-H1944) ASP4132 potently inhibited cell growth, proliferation and cell cycle progression as well as cell migration and invasion. Robust apoptosis activation was detected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 76 publications
(53 reference statements)
1
38
0
Order By: Relevance
“…Recent studies have identified a mitochondria-dependent pathway of programmed necrosis, 39 - 43 . A number of anti-cancer agents could provoke the programmed necrosis cascade, contributing to cancer cell death 44 - 48 . The mitochondrial immunoprecipitation (mito-IP) assay results in Figure 3D showed that SKI-V treatment induced p53-CyPD-adenine nucleotide translocator-1 (ANT1) complexation in the mitochondria of pCCa-1 cells, known as the initial step of programmed necrosis cascade induction 39 , 49 , 50 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have identified a mitochondria-dependent pathway of programmed necrosis, 39 - 43 . A number of anti-cancer agents could provoke the programmed necrosis cascade, contributing to cancer cell death 44 - 48 . The mitochondrial immunoprecipitation (mito-IP) assay results in Figure 3D showed that SKI-V treatment induced p53-CyPD-adenine nucleotide translocator-1 (ANT1) complexation in the mitochondria of pCCa-1 cells, known as the initial step of programmed necrosis cascade induction 39 , 49 , 50 .…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of mTOR can result in apoptosis in NSCLC cells [ 24 26 ]. The activities of both caspase-3 and caspase-7 were boosted in pCan1 primary cells treated with CC-115 (100 nM, 24 h) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that CC-115-provoked NSCLC cell death was more dramatic than AZD2014 plus NU7026 combine, we tested other possible mechanisms responsible for CC-115’s actions. A number of anticancer agents, including mTOR inhibitors, can induce oxidative injury and ROS production to exacerbate cancer cell death [ 25 , 26 , 34 , 35 ]. In CC-115 (100 nM, 16 h)-treated pCan1 primary cells, ROS levels were significantly boosted, and the CellROX intensity was robustly augmented (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other methods , including Western blotting, qRT-PCR, CCK-8, colony formation, EdU staining, Transwell assays, TUNEL staining and other apoptosis-related assays were described in the previous studies 25 , 26 . Same set of protein lysates were always run in parallel “sister” gels to test different proteins.…”
Section: Methodsmentioning
confidence: 99%